O-013 Defining the Basis of Epithelial Defects in Crohn's Using Intestinal Spheroid Culture. (March 2016) - VanDussen, Kelli; Miyoshi, Hiroyuki; Sonnek, Naomi; Ciorba, Matthew; Stappenbeck, Thaddeus
Abstract : Background: Defects in intestinal epithelial cells have been observed in Crohn's disease (CD) and are proposed to contribute to its pathogenesis and chronic nature. An unanswered question is whether these defects would continue to be observed once the epithelial cells are removed from their environment. We addressed this question using human epithelial spheroid culture, where primary intestinal epithelial cell lines are established from biopsy tissue, and a CD-associated epithelial gene signature that we previously observed in ∼75% of CD ileal resection tissue specimens. We also took the opportunity to examine inter-individual variation in spheroid lines generated from different patients and cultured in different conditions. Methods: We selected 38 ileal spheroid lines (19 CD and 19 controls without IBD) generated from tissue regions without active disease by endoscopic analysis. Spheroid lines were grown as enriched for stem cells or differentiated to enterocytes or wound-associated epithelial cells using distinct media. RNA was isolated from the cultured cells and biopsy tissue collected from the same patients at the same time for transcriptional analysis with a custom-designed Fluidigm assay for the CD-associated epithelial gene signature or Agilent microarrays. Morphological assessment was performed with ImageJ. Results: The CD-associated gene signature was observed in 50% of the CD biopsy samples, but was not maintained in cultured spheroids from the same patients. Thus, a persistent factor in the in vivo environment is likely the biological basis of this defect. Unsupervised hierarchical clustering of the microarray data showed a large transcriptional shift in the differentiated enterocytes and wound-associated epithelial (WAE) cell spheroids as compared to stem cell-enriched spheroids. Inter-individual variation was not obvious in stem cell samples, which nearly all clustered together. In contrast, the WAE cell samples formed multiple distinct clusters, suggesting that inter-individual variation is present in this growth condition. We previously observed that mouse intestinal spheroids exhibited a robust increase in area in the WAE cell medium. There was a similar response in human ileal spheroids, with a 1.9-fold average increase in spheroid area in WAE cell compared to stem cell media. This response was highly variable, ranging from no change to a 3-fold area increase in cell lines generated from different patients. Neither the transcriptional nor morphological phenotypes were dependent on patient diagnosis. Conclusions: We have examined a large number of intestinal spheroid lines and demonstrated that some epithelial phenotypes persist in culture whereas others do not. Inter-individual variation was evident in human spheroid lines generated from different patients in certain culture conditions. Thus, human spheroid lines are a very promising tool for understanding the basis of epithelial defects in Crohn's. Moreover, these results show that researchers will need to take care when selecting human intestinal spheroid lines for use in their studies.